Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $X\sim \text{Geo}(1/4), Y\sim \text{Geo}(1/2)$ be given. First I have to compute $\mathbb{E}[z^{X+Y}]$: $$\mathbb{E}[z^{X+Y}]=\mathbb{E}[z^{X}]\cdot\mathbb{E}[z^{Y}]=\frac{\frac{1}{4}z}{1-\left(1-\frac{1}{4}\right)z}\cdot\frac{\frac{1}{2}z}{1-\left(1-\frac{1}{2}\right)z}=\frac{z^2}{8\left(1-\frac{1}{2}z\right)\left(1-\frac{3}{4}z\right)}.$$ The next task is to find $\alpha,\beta,\gamma\in\mathbb{R}$ such that $$\mathbb{E}[z^{X+Y}]=\alpha+\frac{\beta}{1-\frac{1}{2}z}+\frac{\gamma}{1-\frac{3}{4}z}.$$ Here is my procedure (which seems to be wrong...): $$\frac{z^2}{8\left(1-\frac{1}{2}z\right)\left(1-\frac{3}{4}z\right)}=1+\frac{10z-8}{8\left(1-\frac{1}{2}z\right)\left(1-\frac{3}{4}z\right)}$$ $$\frac{10z-8}{8\left(1-\frac{1}{2}z\right)\left(1-\frac{3}{4}z\right)}=2\cdot\frac{5z-4}{(z-2)(3z-4)}=\frac{A}{z-2}+\frac{B}{3z-4}$$ $$\frac{A(3z-4)+B(z-2)}{(z-2)(3z-4)}=\frac{(3A+B)z+(-4A-2B)}{(z-2)(3z-4)}$$ $$\left.\begin{cases} 3A+B&=5 \\ -4A-2B&=-4 \end{cases}\right\}\implies A=3,\;B=-4\implies 2A=6,\;2B=-8$$ $$\rightsquigarrow \mathbb{E}[z^{X+Y}]=1+\frac{6}{z-2}-\frac{8}{3z-4}=1-\frac{3}{1-\frac{1}{2}z}+\frac{2}{1-\frac{3}{4}z}\implies\alpha=1,\;\beta=-3,\;\gamma=2$$

However it seems that the values for $\alpha,\beta,\gamma$ should each be just a third of my result! Can anyone explain me, what I did wrong?

share|improve this question
1  
The first line, $$\frac{z^2}{8\left(1-\frac{1}{2}z\right)\left(1-\frac{3}{4}z\right)}=1+\frac{10‌​z-8}{8\left(1-\frac{1}{2}z\right)\left(1-\frac{3}{4}z\right)},$$ is off by a factor of $4$. –  anon Jun 11 '12 at 23:02
    
@anon: Thanks. Answered my own question now. –  Christian Ivicevic Jun 11 '12 at 23:17

1 Answer 1

up vote 0 down vote accepted

Due to anons hint (thanks!) I found the mistake.

$$\frac{z^2}{8\left(1-\frac{1}{2}z\right)\left(1-\frac{3}{4}z\right)}=1+\frac{\frac{10}{3}z-\frac{8}{3}}{8\left(1-\frac{1}{2}z\right)\left(1-\frac{3}{4}z\right)}$$

This leads to $\alpha=1/3,\;\beta=-1,\;\gamma=2/3$ which is correct.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.